Atmospheric corrosion of materials and their effects on mechanical properties: A brief review. (2021) - Kumar, Veerendra; Sharma, Nitin; Tiwari, S.K.; Kango, Saurabh
Abstract: The present study aims to review the atmospheric corrosion of engineering materials and their effects on the mechanical properties. There are various environmental factors which affect the atmospheric corrosion such as temperature, humidity, pollutants, particulate matter, oxygen, etc. The concentration and quality of these factors also vary from place to place. These influential factors which affect the atmospheric corrosion and the techniques associated to evaluate the corroded samples have been reviewed from the reported studies. Moreover, the influence of atmospheric corrosion on the mechanical properties such as tensile strength, fatigue has also been discussed. The discussion on surface morphology and rust analysis has also been revealed. It has been observed that the mechanical properties of different materials are highly influenced by atmospheric corrosion. This can be due to the increase in weight loss percentage in the corroded material that leads to diminish the properties. It has also been found that the high concentration of environmental factors and long-time exposure equally participate in the reduction of mechanical properties.